Nas fissuras dos cadernos encardidos: processos de subjetivação e a discursividade literária em Carolina Maria de Jesus - Carrijo, Fabiana Rodrigues (2013)
This research investigated, from a theoretical and methodological analysis rested on the French contributions AD as a subject of a discourse constitutes his subjectivity through the exercise of writing himself. Thus, this thesis listed the singularities of this writing himself especially through two particular diaries of Carolina Maria de Jesus especially Quarto de Despejo (1960). The studies presented in this work intended to discuss the subject as a writing subject that is worth in order to preserve the living day in blanchoniana hope that it should be noted for preserving and preserves itself not to pass unscathed. This problematic subject related with his writing was taken by Foucault presented studies from the notions himself writing, self care from hypomnemata and of lettres de cachet , that allowed to make an inventory of a subject constitution through his writing. In this discursive analysis exercise of a literary basis corpus, from Foucault‟s notions and notations from other theoretical fields (such as literary criticism and Bakhtin‟ studies), it ruled that the subject constitution in various subject-positions produced in and contradiction by himself: nor fully racked, nor spokesman deleted. This working purpose made use of discursivity notion proposed by Orlandi (pecheutiniana influence) and added in it the literary word to specify a writing by itself that signed up in order as a becoming discourse in another one may be from another order. In this sense, the literary term did not take here correlations which would be a literary statute . it was beyond these assignments. This analysis exercise, or still this reading gesture made a objectification process description of a subjectivation as an subject-effect , from writing himself . Corollary to this plural subject constitution, it observed a writing from himself that says not only something more about himself and to evidence a subject constitution by writing himself, singled the essence of a writing from another ones: drunkards, indigents, women that lived in penate while men rejoice with the situation because they are provided by these women.